Collaborative Leadership in Adaptive Governance: A Case Study of Natural Resource-Based Communities - Ardiansyah Ardiansyah; Muhammad Abdul Dzakir (Adaptive Governance Research, 2025)
Purpose: This study explores the dynamics of collaborative leadership within adaptive governance in natural resource–based communities in Lombok, Indonesia. It aims to understand how leadership practices facilitate coordination, participation, and institutional adaptation in managing ecological and social complexity. The research seeks to contribute to management scholarship by identifying leadership processes that enable sustainable governance through cooperation, flexibility, and collective decision-making. Subjects and Methods: Using a qualitative case study approach, the research collected data through in-depth interviews with community leaders, local government officials, and NGO representatives involved in resource management initiatives. Observations and document analyses complemented the interviews to triangulate findings. The data were analyzed thematically, focusing on leadership practices that fostered communication, coordination, and adaptive responses within governance systems. Results: Findings reveal that collaborative leadership emerged as the central mechanism for achieving adaptive governance outcomes. Leaders acted as institutional bridges, facilitating dialogue among diverse stakeholders, harmonizing traditional and formal governance structures, and fostering trust-based participation. Their capacity to adaptively respond to environmental and social challenges strengthened community resilience and sustainability. The study also found that leadership effectiveness depended on relational competence, cultural legitimacy, and the ability to institutionalize learning within governance practices. Conclusions: Collaborative leadership is vital for managing complex socio-ecological systems. It transforms governance into a dynamic process of shared responsibility and continuous adaptation. The study advances management theory by positioning leadership as an adaptive, relational, and systemic process fundamental to sustainable community-based governance.